Education on the role of family to increase knowledge in preventing attacks in post-stroke patients - A. Suyatni Musrah; Anggi Pratiwi; Daniel Suranta Ginting; Dewi Nurhanifah; Muhammad Anshari (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Post-stroke family education is essential in increasing family knowledge and understanding regarding treating and preventing recurrent attacks. Educational strategies can be applied to empower families in caring for family member’s post-stroke. This community service aims to provide family education to increase knowledge in preventing attacks in post-stroke patients. This community service activity is carried out through the planning, implementation, and evaluation stages. Improve their understanding of post-stroke risk factors, symptoms, and preventive measures. The importance of understanding early symptoms and emergency measures is the focus of inviting families to recognize changes in the patient's condition early. It can be concluded that the knowledge and understanding provided to families will enhance their ability to play an active role in preventing post-stroke attacks and creating an environment that supports patient recovery. Family awareness of their crucial role in the care team can positively impact the quality of life of post-stroke patients and reduce the risk of re-occurrence.